Sequence-specific DNA recognition by the myb-like domain of the human telomere binding protein TRF1: a model for the protein-DNA complex. - König, P (1998)
Telomeres consist of tandem arrays of short G-rich sequence motifs packaged by specific DNA binding proteins. In humans the double-stranded telomeric TTAGGG repeats are specifically bound by TRF1 and TRF2. Although telomere binding proteins from evolutionarily distant species are not sequence homologues, they share a Myb-like DNA binding motif. Here we have used gel retardation, primer extension and DNase I footprinting analyses to define the binding site of the isolated Myb-like domain of TRF1 and present a three-dimensional model for its interaction with human telomeric DNA. Our results suggest that the Myb-like domain of TRF1 recognizes a binding site centred on the sequence GGGTTA and that its DNA binding mode is similar to that of the homeodomain-like motifs of the yeast telomere binding protein RAP1. The implications of these findings for recognition of telomeric DNA in general are discussed.